Evaluating the Risk of Irreversible Intestinal Necrosis Among Critically Ill Patients With Nonocclusive Mesenteric Ischemia. (28th July 2021) - Calame, Paul; Winiszewski, Hadrien; Doussot, Alexandre; Malakhia, Alexandre; Grillet, Franck; Verdot, Pierre; Vuitton, Lucine; Ronot, Maxime; Pili-Floury, Sebastien; Heyd, Bruno; Delabrousse, Eric; Piton, Gael
Abstract : INTRODUCTION: To identify factors associated with irreversible transmural necrosis (ITN) among critically ill patients experiencing nonocclusive mesenteric ischemia (NOMI) and to compare the predictive value regarding ITN risk stratification with that of the previously described Clichy score. METHODS: All consecutive patients admitted to the intensive care unit between 2009 and 2019 who underwent exploratory laparotomy for NOMI and who had an available contrast-enhanced computed tomography with at least 1 portal venous phase were evaluated for inclusion. Clinical, laboratory, and radiological variables were collected. ITN was assessed on pathological reports of surgical specimens and/or on laparotomy findings in cases of open–close surgery. Factors associated with ITN were identified by univariate and multivariate analysis to derive a NOMI-ITN score. This score was further compared with the Clichy score. RESULTS: We identified 4 factors associated with ITN in the context of NOMI: absence of bowel enhancement, bowel thinning, plasma bicarbonate concentration ≤15 mmol/L, and prothrombin rate <40%. These factors were included in a new NOMI-ITN score, with 1 point attributed for each variable. ITN was observed in 6%, 38%, 65%, 88%, and 100% of patients with NOMI-ITN score ranging from 0 to 4, respectively. The NOMI-ITN score outperformed the Clichy score for the prediction of ITN (area under the receiver operating characteristics curve 0.882 [95% confidence interval 0.826–0.938] vs 0.674 [95% confidence interval 0.582–0.766], respectively, P < 0.001). DISCUSSION: We propose a new 4-point score aimed at stratifying risk of ITN in patients with NOMI. The Clichy score should be applied to patients with occlusive acute mesenteric ischemia only. Abstract :